The acceptability and feasibility of Acceptance and Commitment Therapy training to support work-related wellbeing for managers of homelessness services - Young, Olivia (2024)
Introduction: Managers of homelessness services have an important role in implementing psychologically informed environments (PIEs), managing staffing levels, dealing with emergencies such as deaths in service and supporting their teams. Given these challenges, it is not surprising that they can be at risk of vicarious traumatisation, burnout, and poor wellbeing. Acceptance and Commitment Therapy (ACT) has been shown to be an effective workplace wellbeing intervention and could be offered to managers of homelessness services. Given the pressure that managers are under working with service pressures, high staff turnover and clients with complex needs it is appropriate they are provided with further support for their wellbeing. However, it is important to assess the feasibility prior to offering it more widely. At present there are no studies which have investigated ACT-based training for managers in homelessness services. Therefore, the aims of this current study were to assess the acceptability and feasibility of an ACT-based training for managers of homelessness services. The training was intended for participants to learn to use ACT to support their work-related and personal wellbeing. Secondary objectives were to assess participant recruitment, retention rates, measure completion and signal efficacy.